Identification of a genomic cluster related to hypersecretion of intestinal mucus and mucinolytic activity of atypical enteropathogenic Escherichia coli (aEPEC) - Trovão, Liana de Oliveira; Vieira, Mônica Aparecida Midolli; Santos, Ana Carolina de Mello; Puño-Sarmiento, Juan Josue; Nunes, Pedro Henrique Soares; Santos, Fernanda Fernandes; Rocha, Victória Galdino Pavlenco; Knöbl, Terezinha; Navarro-Garcia, Fernando; Gomes, Tânia Aparecida Tardelli (Frontiers in Cellular and Infection Microbiology, 2024)
Enteropathogenic Escherichia coli (EPEC) strains are subdivided into typical (tEPEC) and atypical (aEPEC) according to the presence or absence of a virulence-associated plasmid called pEAF. Our research group has previously demonstrated that two aEPEC strains, 0421-1 and 3991-1, induce an increase in mucus production in a rabbit ileal loop model in vivo. This phenomenon was not observed with a tEPEC prototype strain. Few studies on aEPEC strains evaluating their capacity to induce intestinal mucus hypersecretion were done. This study aimed to investigate aEPEC strains regarding their genotypic and phenotypic characteristics, their ability to alter mucus production in an in vivo intestinal infection model, and their potential mucinolytic activity. To investigate the relationship between strains 0421-1 and 3991-1 and 11 other aEPEC strains, their serotypes, sequence types (ST), and virulence factors (VF), several sequencing and genomic analyses were carried out. The study also involved researching the reproduction of mucus hypersecretion in rabbits in vivo. We found that the two mucus-inducing strains and two other strains (1582-4 and 2531-13) shared the same phylogroup (A), ST (378), serotype (O101/O162:H33), and intimin subtype (ι2), were phylogenetically related, and induced mucus hypersecretion in vivo. A wide diversity of VFs was found among the strains, confirming their genomic heterogeneity. However, among the genes studied, no unique virulence factor or gene set was identified exclusively in the mucus-inducing strains, suggesting the multifactorial nature of this phenomenon. The two strains (1582-4 and 2531-13) closely related to the two aEPEC strains that induced mucus production in vivo also induced the phenomenon. The investigation of the mucinolytic activity revealed that all aEPEC strains used mucins as their carbon sources. Ten of the 13 aEPEC strains could cross a mucin layer, and only four adhered better to agar containing mucin than to agar without mucin. The present study paves the way for subsequent investigations into the molecular mechanisms regarding cellular interactions and responses, as well as the correlation between virulence factors and the induction of mucus production/expression during aEPEC infections.